2020
DOI: 10.3390/catal10121477
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Sintering of Nickel Particles Supported on γ-Alumina under Hydrothermal Conditions

Abstract: Sintering of nickel particles is a well-known path of deactivation for Ni/Al2O3 catalysts. Considering the CO2 methanation in the context of Power-to-Gas, a sintering study for up to 300 h was performed in a controlled atmosphere between 450 and 600 °C. Since water is a product of the methanation reaction and is known to favor the particle sintering, the H2O:H2 molar ratio was varied in the range 0–3.2. Characterization of the post mortem samples showed sintering of both nickel and support particles. The absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For TEM images, the average metal particle size was obtained from several measurements in two orthogonal directions. A sample of 30 particles found a growth in average metal particle size from 6.5 nm for a sample aged for 20 h up to 10.5 nm for a sample aged for 100 h. [57] CO 2 conversions and CH 4 yields of catalysts after hydrothermal aging of different periods are shown in Fig. 3.…”
Section: Sinteringmentioning
confidence: 97%
See 3 more Smart Citations
“…For TEM images, the average metal particle size was obtained from several measurements in two orthogonal directions. A sample of 30 particles found a growth in average metal particle size from 6.5 nm for a sample aged for 20 h up to 10.5 nm for a sample aged for 100 h. [57] CO 2 conversions and CH 4 yields of catalysts after hydrothermal aging of different periods are shown in Fig. 3.…”
Section: Sinteringmentioning
confidence: 97%
“…This confirms the general opinion that sintering of nickel particles is a major cause of deactivation for methanation catalysts. [57] Champon et al determined the loss of metal surface due to sintering of metal particles by measuring metal surfaces with hydrogen chemisorption and temperature-programmed desorption (H 2 -TPD). They adapted the GPLE previously proposed by Fuentes [51] taking into account that higher H 2 O/H 2 ratios promote sintering [57]:…”
Section: Sinteringmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also reported the formation of nickel aluminate (NiAl 2 O 4 ) and nickel oxide (NiO) at high temperatures and P H2O /P H2 . Champon et al [28] showed that an increase in the H 2 O/H 2 ratio results in increased sintering of Ni, which was successfully modelled by a generalised power-law expression.…”
Section: Introductionmentioning
confidence: 99%